A centrifuge-based flight simulator: Optimization of a baseline acceleration profile based on the motion sickness incidence. (November 2019) - Lewkowicz, Rafał
Abstract: Simulator sickness is a common problem when using centrifuge-based flight simulator. During centrifuge-based training, achieving a G-baseline level and returning to a complete stop after each G-profile still cause unpleasant sensations and motion sickness. The aim of this study was to determine the optimal G-baseline level and the optimal approach motion cueing when the centrifuge-based flight simulator achieved and returned from this G-baseline level. A model of motion sickness incidence (MSI) was used to elucidate the optimal solution of motion cueing. The motion stimuli were computed based on an inverse kinematics model of the centrifuge-based motion system. For each analysed G-baseline profile, there were stimuli that provoked the occurrence of MSI. These stimuli were directly proportional to the applied G-onset rate. There was found the optimal G-baseline level at 1.41 G and optimal motion cueing (0.05 G s −1 ) that gave the minimal MSI. Up to 41% and 32% a reduction in the MSI could be obtained during the achievement and return from this G-baseline level, respectively. In order to confirm obtained results further studies should be performed with participants in an actual centrifuge-based flight simulator. Highlights: The optimal G-baseline, during the transition to and from the higher-G, is 1.4 G. For the optimal motion cueing the smaller the G-onset rate, the smaller the MSI. During approach the G-baseline a reduction of 41% in the MSI can be obtained. During return from the G-baseline a reduction of 32% in the MSI can be obtained. There is only one optimal stimulus pattern – G-onset rate (0.05 G s −1 ).